Batteries, compressed air, flywheels, or pumped hydro? Exploring public attitudes towards grid-scale energy storage technologies in Canada and the United Kingdom. (October 2021) - Jones, Christopher R.; Hilpert, Peter; Gaede, James; Rowlands, Ian H.
Abstract: Grid-scale electrical energy storage technologies (GESTs) – like compressed air energy storage (CAES), flywheels, lithium ion batteries, and pumped hydro storage – will play a key role in the decarbonisation of national electricity systems. While the public acceptability of energy infrastructure is important, little is known about public attitudes towards GESTs. This study presents the findings of an online survey ( N = 2058), based upon the Comprehensive Technology Acceptance Framework, designed to provide insight into the nature of public attitudes towards GEST deployment in two Western industrialised nations, Canada ( n = 1014) and the United Kingdom ( n = 1044). We show here that public attitudes towards GESTs are positive in both countries. Participants showed a relative preference for pumped hydro (37–40% favoured this option) versus batteries (23–25%), compressed air (13–17%), flywheels (14%), or none (8–10%). Structural equation modelling was used to identify the predictors of general attitudes towards GEST deployment. General attitudes were directly predicted by positive and negative affect, perceived risks and benefits, and trust in developers. We also show that trust in developers and environmental worldviews are significant mediated predictors of general attitudes, and that our overall model of general attitudes was comparable within both countries. The findings hold implications for the design and delivery of public engagement and communication programmes pertaining to GESTs. They confirm the need to employ trusted communicators, reflect the potential value to using environmentally-framed messaging, and advocate in favour of approaches that both respond to the genuine concerns of citizens and are designed to promote more informed public discourse about their inclusion (or exclusion) in national electricity networks.